H HUBUNGAN TRIASE PASIEN DENGAN TINGKAT KECEMASAN KELUARGA YANG DI RAWAT DI IGD - Huzaifah, Zaqyyah (LPPM Universitas Sari Mulia, 2022)
Background: Due to the large number of patient visits to the Emergency Room, a triage system is needed to sort out patients who are prioritized to get service first to anticipate patient density and avoid patients not being helped or dying due to not getting help quickly. The distribution of triage is one of the common causes for families to feel anxious, especially if the family does not understand the triage system used, they will feel neglected and fear if their family members do not get immediate health care. Objective: This study aims to determine the relationship between patient triage and family anxiety levels in the Emergency Room. Method: This study used a qualitative approach with cross sectional design and 107 people. Sampling technique using Consecutive Sampling. Result: Statistical test results using Spearman Rank obtained p value = 0.012. Conclusion: There is a relationship triage of patients with family anxiety levels in the Emergency Room.